Anaesthesiologic Considerations for Intraoperative ECMO Anticoagulation During Lung Transplantation: A Single-Centre, Retrospective, Observational Study - Vajter, Jaromir; Holubova, Gabriela; Novysedlak, Rene; Svorcova, Monika; Vachtenheim, Jiri; Vymazal, Tomas; Lischke, Robert (Transplant international, 2024)
Background: Extracorporeal membrane oxygenation (ECMO) is frequently used during lung transplantation. Unfractionated heparin (UFH) is mainly used as part of ECMO support for anticoagulation. One of the most common perioperative complications is bleeding, which high-dose UFH can aggravate. Methods: We retrospectively analyzed ( n = 141) patients who underwent lung transplantation between 2020 and 2022. All subjects ( n = 109) underwent central cannulated VA ECMO with successful intraoperative ECMO weaning. Patients on ECMO bridge, postoperative ECMO, heart-lung transplants and transplants without ECMO were excluded. The dose of UFH for the entire surgical procedure, blood loss and consumption of blood derivatives intraoperatively and 48 h after ICU admission were recorded. Surgical revision for postoperative bleeding were analyzed. Thrombotic complications, mortality and long-term survival were evaluated. Results: Lower doses of UFH administered for intraoperative ECMO anticoagulation contribute to a reduction in intraoperative blood derivates consumption and blood loss with no thrombotic complications related to the patient or the ECMO circuit. Lower doses of UFH may lead to a decreased incidence of surgical revision for hemothorax. Conclusion: Lower doses of UFH as part of intraoperative ECMO anticoagulation might reduce the incidence of complications and lead to better postoperative outcomes.